2021
DOI: 10.1007/s00426-021-01556-9
|View full text |Cite
|
Sign up to set email alerts
|

Mnemonic attention in analogy to perceptual attention: harmony but not uniformity

Abstract: We have no known conflict of interest to disclose. We thank Yichen Wang, Yuhang Li and Yajing Wang for experimental assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…This parallels prior studies that employed perceptual memoranda, which have shown larger RCEs on reaction times for voluntary compared to involuntary attention (Shimi et al, 2014;van Ede et al, 2020; but see Berryhill et al, 2012;Han & Ku, 2022). The present study extends these findings by showing that this voluntary advantage persists even when the effects of involuntary attention are ruled out, given the independent assessment of both attentional types, underscoring the substantial potential of voluntary attention in prioritizing internal contents for retrieval.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This parallels prior studies that employed perceptual memoranda, which have shown larger RCEs on reaction times for voluntary compared to involuntary attention (Shimi et al, 2014;van Ede et al, 2020; but see Berryhill et al, 2012;Han & Ku, 2022). The present study extends these findings by showing that this voluntary advantage persists even when the effects of involuntary attention are ruled out, given the independent assessment of both attentional types, underscoring the substantial potential of voluntary attention in prioritizing internal contents for retrieval.…”
Section: Discussionsupporting
confidence: 90%
“…Fourthly, the present RCE persisted irrespective of the type of WM contents, which indicates voluntary mechanisms of retrieval operate regardless of the quality and nature of the WM representation. Lastly, regarding involuntary attention, it is important to note that two studies (Han & Ku, 2022;Shimi et al, 2014) evidenced RCEs on reaction times by employing peripheral retro-cues. In contrast, in van Ede and colleagues' study (2020) and the present investigation, no such effects of involuntary attention were observed by using central retro-cues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations